2010
DOI: 10.1021/pr1006087
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Protein−Protein Interactions within the Cysteine Sulfinate Desulfinase Fe−S Cluster Biogenesis System

Abstract: Fe-S cluster biogenesis is of interest to many fields, including bioenergetics and gene regulation. The CSD system is one of three Fe-S cluster biogenesis systems in E. coli and is comprised of the cysteine desulfurase CsdA, the sulfur acceptor protein CsdE, and the E1-like protein CsdL. The biological role, biochemical mechanism, and protein targets of the system remain uncharacterized. Here we present that the active site CsdE C61 has a lowered pK a value of 6.5, which is nearly identical to that of C51 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 98 publications
5
21
0
Order By: Relevance
“…Thus, the structural analysis of CsdA-CsdE further supports the notion that CsdA/CsdE and SufS/SufE work similarly and that the proteins may have been derived from a common ancestor. Thus, CsdE and SufE likely share some of the protein interactomes as demonstrated by others (36).…”
Section: Resultssupporting
confidence: 54%
“…Thus, the structural analysis of CsdA-CsdE further supports the notion that CsdA/CsdE and SufS/SufE work similarly and that the proteins may have been derived from a common ancestor. Thus, CsdE and SufE likely share some of the protein interactomes as demonstrated by others (36).…”
Section: Resultssupporting
confidence: 54%
“…Apart from this, upregulation of several genes encoding for toxin production and secretions ( sat, yjg K, chp S, chp B and ygj N) was observed in ocular E. coli biofilm cells which is an important factor that governs the virulence in pathogenic bacterial cells. Virulence of ocular E. coli may also be related to up regulation of Lipid A moiety of LPS, a potent stimulator of the immune system and a trigger of intense inflammation in the host cells [61]. Many genes encoding for proteins that influence antigen presentation ( wzz B and waa L), extracellular matrix remodeling ( yii X), transport of aminoacids and other metabolites ( cbr B, cbr C, his I and mgl B) are also up regulated in ocular E. coli in biofilm stage and may have a role to play in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes encoding for proteins that influence antigen presentation ( wzz B and waa L), extracellular matrix remodeling ( yii X), transport of aminoacids and other metabolites ( cbr B, cbr C, his I and mgl B) are also up regulated in ocular E. coli in biofilm stage and may have a role to play in virulence. Costa et al [61] have recently suggested that in E. coli, during biofilm formation on abiotic surfaces, cells are exposed to several DNA damaging agents against which the cells need to be protected. In the present study gene ira D, uvr D and rec C involved in DNA damage repair are up regulated and could be acting to ensure survival of cells faced with oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…52 Along these lines, E. coli Grx4 has been shown to form a disulfide with the sulfur trafficking proteins CsdE and SufE in vivo , linking Grx4 function with regulation of sulfur trafficking. 59, 60 Thus, IbaG/BolA may potentially regulate the activity of Grx4 via binding and/or blocking of the redox-active cysteine.…”
Section: Discussionmentioning
confidence: 99%